2010
DOI: 10.1152/ajpendo.00317.2009
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of electron transport chain in human skeletal muscle mitochondria in type 2 diabetes mellitus and obesity

Abstract: Ritov VB, Menshikova EV, Azuma K, Wood R, Toledo FG, Goodpaster BH, Ruderman NB, Kelley DE. Deficiency of electron transport chain in human skeletal muscle mitochondria in type 2 diabetes mellitus and obesity. Am J Physiol Endocrinol Metab 298: E49 -E58, 2010. First published November 3, 2009 doi:10.1152/ajpendo.00317.2009.-Insulin resistance in skeletal muscle in obesity and T2DM is associated with reduced muscle oxidative capacity, reduced expression in nuclear genes responsible for oxidative metabolism, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
193
2
3

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 253 publications
(221 citation statements)
references
References 67 publications
(94 reference statements)
16
193
2
3
Order By: Relevance
“…Moreover, significant positive correlations were also observed for summative spot volumes (sum of volumes of all spots with the same identified protein) relating to cytoplasmic malate dehydrogenase (MDH1), an enzyme controlling TCA cycle pool size and providing contractile function [27], and the mitochondrial enzymes ACO2, ATP5A1, ATP5B and GBAS. These results, suggesting reduced TCA cycle and mitochondrial protein content in insulin resistance, are consistent with previous findings of reduced enzyme activities [10,28,29], protein expression [16,17,30], altered phosphorylation [16,31,32], altered transcript levels [10,33,34] or altered flux through mitochondrial ATP synthase [8].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, significant positive correlations were also observed for summative spot volumes (sum of volumes of all spots with the same identified protein) relating to cytoplasmic malate dehydrogenase (MDH1), an enzyme controlling TCA cycle pool size and providing contractile function [27], and the mitochondrial enzymes ACO2, ATP5A1, ATP5B and GBAS. These results, suggesting reduced TCA cycle and mitochondrial protein content in insulin resistance, are consistent with previous findings of reduced enzyme activities [10,28,29], protein expression [16,17,30], altered phosphorylation [16,31,32], altered transcript levels [10,33,34] or altered flux through mitochondrial ATP synthase [8].…”
Section: Discussionsupporting
confidence: 92%
“…Inflammation and cytokine signalling appear to be important, and recent studies have linked insulin resistance with mitochondrial dysfunction. This includes reduced mitochondrial content and in some [2][3][4][5], but not all, studies, reduced mitochondrial functional capacity [2,4,[6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Elevated NADH levels indicate that the catabolism in muscle has been enhanced and can facilitate the ETC process, which can further cause oxidative stress (Kussmaul and Hirst, 2006). A high ratio of NADH/NAD is desirable in an anaerobic tissue, which is usually caused by the production of reactive oxygen species in an aerobic tissue that inhibits the tricarboxylic acid cycle and fatty acid oxidation (Ritov et al, 2010;James et al, 2012). The present results showed that LPS treatment caused an increased tendency in the ratio of NADH/NAD.…”
Section: Discussionmentioning
confidence: 55%
“…1 -3 Changes in mitochondrial sequence may influence obesity by tightly coupling mitochondrial electron transport, or by interfering with mitochondrial function with subsequent diversion of dietary energy sources towards fat synthesis. 4 Studies of mitochondrial haplogroups, clusters of haplotypes emerging along ancient patterns of human migration, have also suggested a role for sequence variation in environmental adaptations. 5 Conversely, obesity has been widely demonstrated to interfere with mitochondrial function.…”
Section: Introductionmentioning
confidence: 99%